Kimika Industrial Corporation: A strategic management paper - Yu, Audris Hazel O. (Animo Repository, 2008)
Kimika Industrial Corporation belongs to the engineering plastics segment under the Plastics industry and its vision is to be known in the Philippines as the BEST PROVIDER of high quality engineering plastics. Its Core Purpose for the last 31 years is to provide the market with a wide range of engineering plastics of high quality. To achieve its vision and continue to fulfill its mission, its corporate objectives are to increase net income by P100,000 in 2008, P200,000 in 2009, and P300,000 in 2010 and to increase market share by 20% in 2010. To accomplish this objective, below is the strategy of KIC: Strategy : Expand geographical scope to Northern Luzon, Visayas, and Mindanao The basis of KIC's strategy comes from the 4 factors: First Basis is the Threats and Opportunities to the Plastics Processing Industry. Threats to this industry would come from the following: Asian Free Trade Agreement Environmental Issues regarding the use of non biodegradable products Opportunities to this industry would come from the following: The issuance of Executive Order No. 486 brought down the tariff on imported raw materials to 5% from its previous rate of 10%. Growth in the automotive industry GDP growth rate Second Basis is the Strengths and Weaknesses of the Organization. The Strengths of Kimika Industrial Corporation as an organization would come from Sourcing of Supplier for Engineering Plastics, and Wider variety of Engineering Plastics. Its Weakness would come from Late deliveries and manual tracking of inventory. Third Basis is the expectation of society. KIC has taken the role of Corporate Social Responsibility. Fourth Basis is the family values of Key Implementers. The personal values of the owner would be integrity, professionalism, product quality, customer satisfaction, and economical. KICs competitive advantages over its competitors are the following: Wider selection of products Quality at competitive prices For KICs strategy to have the capability for execution it must use the McKinsey 7-S Framework and for the strategy to be implemented it must use the eight Strategy Implementing Tasks or the 8-SIT Framework This is the executive summary of this Strategic Management Paper for KIC.